Serum ghrelin and obestatin levels in patients with acne vulgaris: are they important for the severity? - Kanat, Zekiye (Postepy Dermatol Alergol, 2019)
INTRODUCTION: Acne vulgaris (AV) is a chronic, inflammatory disease of the pilosebaceous unit. Recently, three peptide-structured hormones, products of a single gene, have been discovered. These hormones are acylated ghrelin, des-acyl ghrelin and obestatin. AIM: To demonstrate the association of serum acylated ghrelin, des-acyl ghrelin, and obestatin levels with acne severity. MATERIAL AND METHODS: A total of 63 patients grouped as mild (n = 22), moderate (n = 21) and severe (n = 20) acne according to the Global Acne Grading System and 20 medically healthy volunteers were included in the study. Serum ghrelin and obestatin levels obtained from the participants were examined. RESULTS: When mean ghrelin, des-acyl-ghrelin and obestatin values of the acne-group (AG) were compared with the control group (CG), they were found be lower in the AG, but were not statistically significant. Among the patient groups, while acylated ghrelin values were highest in the severe AG, des-acyl ghrelin values were highest in mild severe AG and mean obestatin values were highest in moderate severe AG (p > 0.05). When the groups were compared for obestatin values; the highest average value was detected in the CG. However, it was not significant when the groups were compared. CONCLUSIONS: It has been suggested that there may be a link between acne and the levels of acylated ghrelin, des-acyl ghrelin and obestatin which are decreased in the serum of acne patients. Because of the decrease observed in the levels of these hormones which have antimicrobial features, we suggest that inflammation in acne cannot be suppressed and the reproduction of the microorganisms that play a role in the aetiology of the disease cannot be prevented. The replacement of these hormones at physiologic concentrations may contribute to the acne treatment.